2017
DOI: 10.18865/ed.27.4.443
|View full text |Cite
|
Sign up to set email alerts
|

Use of Internet for General and Dental Health along Acculturation Features in a Sample of Mexican Americans

Abstract: The objectives of this study were to explore self-reported Internet and electronic platforms used to search for and store medical and dental information among people of Mexican origin. A sample of adults self-identified as European American (250) and as Mexican American (255), residing in Central Indiana, answered a one-time survey that included technology use questions and measured acculturation via the Psychological-Behavioral Acculturation Scale. Overall use of information technologies was estimated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The reasons for this difference are unknown and should be explored in future research. Research has found that Hispanics with low levels of acculturation may access information differently and have different needs than Hispanics with higher levels of acculturation [54,55]. The use of remote peer mentors to encourage behavior change has been found to promote behavior change among patients with diabetes receiving care in a net healthcare delivery setting [56].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this difference are unknown and should be explored in future research. Research has found that Hispanics with low levels of acculturation may access information differently and have different needs than Hispanics with higher levels of acculturation [54,55]. The use of remote peer mentors to encourage behavior change has been found to promote behavior change among patients with diabetes receiving care in a net healthcare delivery setting [56].…”
Section: Discussionmentioning
confidence: 99%